Palm oil shell aggregate as cool pavement by replacing fine aggregate - Mohd Anuar, Mohd Aliff (2018)
Urban Heat Island (UHI) phenomenon is due to ever increasing environment temperature in cities compared to the adjacent non-urbanized areas. One of the major contributors to UHI is asphalt pavement because of its tendency to absorb high amount of heat due to its dark color. Cool pavement is known as a paving material that can reduce surface temperature due to its ability to reflect more solar energy, enhance water evaporation and being altered to be less heat absorbent. Palm Oil Shell Aggregate (POSA) is the material that is identified as having a potential to be the cool pavement due to the presence of Near Infrared Region (NIR) reflective component and void after POSA is replaced in asphalt pavement. Therefore, the study is aimed to apply POSA material as the new cool pavement technology. The investigation involves both physical and chemical properties of POSA, physical performance of asphalt pavement and thermal performance of pavement surface temperature. Various percentage of POSA as fine aggregate replacement which are 10% (P10), 20% (P20), 30% (P30), 40% (P40) and 50% (P50) were mixed into asphalt pavement for subsequent experiment and compared with control sample (CS). The result demonstrated POSA’s particle density value at 1.6mg/m3 and specific gravity value of 1.6, fulfil the minimum requirement by AASHTO which is 1.0. The X-Ray Fluorescence (XRF) analysis showed the chemical element content in POSA are SiO2 (46.41wt%), Fe2O3 (34.01wt%), Al2O3 (7.74wt%) and TiO2 (0.22wt%). Thus, these pure elements of POSA are considered high in NIR reflective agent. All tested samples met the minimum requirement for Marshall stability test. All modified pavement exhibits different performances thus the least susceptibility for modified mixture in resilient modulus is P10 sample. Furthermore, results for dynamic creep show P10, P20 and P30 are recommended for heavily trafficked roads. However, P40 and P50 are more suitable in lightly trafficked road. Thermal performance showed the P50 sample obtaining highest surface temperature reduction of up to 3.29°C compared to CS during peak periods. Statistical analysis showed the ANOVA mean surface temperature indicates a significant reduction of pavement surface temperature due to increased amount of POSA as fine aggregate replacement. Overall finding concludes that P10, P20, P30, P40 and P50 as having a good potential to be used as cool material for paving based on its thermal performance on trafficked road. Thus, the material could be used to mitigate UHI and develop a new idea for cool pavement technology.